PENGEMBANGAN E-MODUL PADA MATA PELAJARAN ADMINISTRASI INFRASTRUKTUR JARINGAN (AIJ) KELAS XI TKJDI SMK NEGERI 1 RAO SELATAN - Afrida Yanti; Ami Anggraini Samudra; Anggri Yulio Pernanda (STMIK KAPUTAMA, 2023)
The purpose of this study is to develop e-module-based learning media using the Sigit editor software. Development of learning media based on e-modules in AIJ subjects that are valid and practical. Based on the problems previously described, this type of research uses the R&D (Research and Development) development research model which aims to produce application products and test the effectiveness of these products. The results of research on the development of E-modules in AIJ subjects that have been tested for the validity of developing E-modules in AIJ Class XI TKJ subjects at SMK Negeri 1 Rao Selatan, state that the e-module is very valid, namely material validity is 0.9 and media validity is 0.822 and the practicality test for the development of E-modules in the AIJ Class XI TKJ subject at SMK Negeri 1 Rao Selatan, declared practical by the teacher and with 100% practicality and 86.6% students.